Long-term X-ray observations of seyfert 1 galaxy ark 120: on the origin of soft-excess. Issue 3 (14th June 2021) - Nandi, Prantik; Chatterjee, Arka; Chakrabarti, Sandip K; Dutta, Broja G
ABSTRACT: We present the long-term X-ray spectral and temporal analysis of a 'bare-type AGN' Ark 120. We consider the observations from XMM–Newton, Suzaku, Swift, and NuSTAR from 2003 to 2018. The spectral properties of this source are studied using various phenomenological and physical models present in the literature. We report (a) the variations of several physical parameters, such as the temperature and the optical depth of the electron cloud, the size of the Compton cloud, and the accretion properties for the last 15 yr. The spectral variations are explained from the changes in the accretion dynamics; (b) the X-ray time delay between 0.2–2 and 3–10 keV light-curves exhibited zero-delay in 2003, positive delay of 4.71 ± 2.1 ks in 2013, and negative delay of 2.90 ± 1.26 ks in 2014. The delays are explained considering Comptonization, reflection, and light-crossing time; (c) the long-term intrinsic luminosities, obtained using nthcomp, of the soft-excess and the primary continuum show a correlation with a Pearson correlation coefficient of 0.90. This indicates that the soft-excess and the primary continuum originate from the same physical process. From a physical model fitting, we infer that the soft excess for Ark 120 could be due to a small number of scatterings in the Compton cloud. Using Monte Carlo simulations, we show that indeed the spectra corresponding to fewer scatterings could provide a steeper soft-excess power law in the 0.2–3 keV range. Simulated luminosities are found to be in agreement with the observed values.